2015
DOI: 10.1111/jam.12964
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Cronobacter sakazakii in reconstituted infant formula by combination of thymoquinone and mild heat

Abstract: These findings suggested that TQ, together with mild heat, may have potential application in infant formula to control C. sakazakii before consumption and therefore is a possible way to prevent infections associated with C. sakazakii in infant formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Cell membrane integrity was determined according to the method described by Alakomi et al with slight modification [ 20 ], using the LIVE/DEAD ® Bac Light ™ Bacterial Viability Kit (Molecular Probes, Eugene, OR). The overnight culture of C .…”
Section: Methodsmentioning
confidence: 99%
“…Cell membrane integrity was determined according to the method described by Alakomi et al with slight modification [ 20 ], using the LIVE/DEAD ® Bac Light ™ Bacterial Viability Kit (Molecular Probes, Eugene, OR). The overnight culture of C .…”
Section: Methodsmentioning
confidence: 99%
“…The QS indicator strain Chromobacterium violaceum ATCC 12472 (ATCC) was used for QS inhibition assays 54 . All C. sakazakii strains were grown and prepared as described before 55 .…”
Section: Methodsmentioning
confidence: 99%
“…A recent report (Sharma et al, 2016) showed that TQ has synergistic antimicrobial activity with other essential oil components (cinnamaldehyde, thymol, and eugenol) against both planktonic and biofilm-associated Staphylococcus epidermidis . Shi et al (2015) also demonstrated that TQ shows antimicrobial activity against Cronobacter sakazakii in reconstituted infant formula.…”
Section: Introductionmentioning
confidence: 97%